Exploring the Anthropometric, Cardiorespiratory, and Haematological Determinants of Marathon Performance - Christou, Georgios A.; Pagourelias, Efstathios D.; Deligiannis, Asterios P.; Kouidi, Evangelia J. (Frontiers in Physiology, 2021)
Aim We aimed to investigate the main anthropometric, cardiorespiratory and haematological factors that can determine marathon race performance in marathon runners. Methods Forty-five marathon runners (36 males, age: 42 ± 10 years) were examined during the training period for a marathon race. Assessment of training characteristics, anthropometric measurements, including height, body weight (n = 45) and body fat percentage (BF%) (n = 33), echocardiographic study (n = 45), cardiopulmonary exercise testing using treadmill ergometer (n = 33) and blood test (n = 24) were performed. We evaluated the relationships of these measurements with the personal best marathon race time (MRT) within a time frame of one year before or after the evaluation of each athlete. Results The training age regarding long-distance running was 9 ± 7 years. Training volume was 70 (50–175) km/week. MRT was 4:02:53 ± 00:50:20 h. The MRT was positively associated with BF% (r = 0.587, p = 0.001). Among echocardiographic parameters, MRT correlated negatively with right ventricular end-diastolic area (RVEDA) (r = −0.716, p < 0.001). RVEDA was the only independent echocardiographic predictor of MRT. With regard to respiratory parameters, MRT correlated negatively with maximum minute ventilation indexed to body surface area (VEmax/BSA) (r = −0.509, p = 0.003). Among parameters of blood test, MRT correlated negatively with haemoglobin concentration (r = −0.471, p = 0.027) and estimated haemoglobin mass (Hbmass) (r = −0.680, p = 0.002). After performing multivariate linear regression analysis with MRT as dependent variable and BF% (standardised β = 0.501, p = 0.021), RVEDA (standardised β = −0.633, p = 0.003), VEmax/BSA (standardised β = 0.266, p = 0.303) and Hbmass (standardised β = −0.308, p = 0.066) as independent variables, only BF% and RVEDA were significant independent predictors of MRT (adjusted R2 = 0.796, p < 0.001 for the model). Conclusions The main physiological determinants of better marathon performance appear to be low BF% and RV enlargement. Upregulation of both maximum minute ventilation during exercise and haemoglobin mass may have a weaker effect to enhance marathon performance. Clinical Trial Registration www.ClinicalTrials.gov, identifier NCT04738877.